Argument structure representation and theory - Freeman, James B.; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
This monograph presents a method of diagramming argument macrostructure, synthesizing the standard circle and arrow approach with the Toulmin model. A theoretical justification of this method through a dialectical understanding of argument, a critical examination of Toulmin on warrants, and a thorough discussion of the linked-convergent distinction follows. Discussion includes consideration of alternative understandings of  argument structure and its representation presented in Wigmore?s chart method, Pollock?s inference graphs, and the pragma-dialectical approach to argumentation. An account of the proper reconstruction of enthymemes and issues at the border of structural analysis versus evaluation of arguments conclude the book.
An approach to argument macrostructure -- The dialectical nature of argument -- Toulmin's problematic notion of warrant -- The linked-convergent distinction, a first approximation -- Argument structure and disciplinary perspective : the linked-convergent versus multiple-co-ordinatively compound distinctions -- The linked-convergent distinction, refining the criterion -- Argument structure and enthymemes -- From analysis to evaluation.
Electronic reproduction.
Keywords: Reasoning; Logic; Grammar, Comparative and general -- Verb phrase; Grammar, Comparative and general -- Syntax; Electronic books